A Decomposition Technique For Solving Integer Programming Problems - Hossain, Md. Istiaq; Hasan, M Babul (GANIT: Journal of Bangladesh Mathematical Society, 2014)
Dantzig-Wolfe decomposition as applied to an integer program is a specific form of problem reformulation that aims at providing a tighter linear programming relaxation bound due to the non-convexity of an integer problem. In this paper, we develop an algorithm for solving large scale integer program relying on column generation method. We implemented our algorithm for solving Capital budgeting and scheduling type problems. Moreover, we used the Computer Aided System (CAS) AMPL to convert our algorithm into programming codes and illustrated the same problem in our program. We demonstrate our method by illustrating some numerical examples. DOI: http://dx.doi.org/10.3329/ganit.v33i0.17649 GANIT J. Bangladesh Math. Soc.Vol. 33 (2013) 1-11